PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR IPA KELAS IV SDN 006 RAJA BEJAMU - Zulfan Efendi; Eddy Noviana; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this research is to know the application of STAD cooperative learning model to improve student learning result of science class IV SDN 006 Raja Bejamu. Student learning outcomes have not shown the expected results, the learning outcome is only 44%. The type of research is class action research consisting of 4 stages of planning, observation, action and reflection. The variable measured in this study is learning outcomes measured using a test. Application of STAD type learning model can improve the average of student learning outcomes from 69.44 to 77.08. This study also measured teacher and student activity using observation sheets. Teacher activity increased from 58.53% to 91.67% and student activity also increased from 50% to 87.5%.Keyword: cooperatif learning , STAD, Learning Outcome IPA.